Incorporating divine command theory in the world of accountants’ professional codes of conduct based on Abrahamic religions - Khalil, Ala’a Mustafa Deeb (2016)
Humanizing humans should be the substantial goal for all scholars in the varied disciplines of social science. Living in a value-free society is becoming a big challenge for the survival of both individuals and societies, in all aspects of humans‘ lives. On the financial level, financial crisis and accounting scandals as a result of fraudulent activities sound the alarm that the recent professional codes of conduct failed to influence the ethical behaviour of practitioners. Adopting spiritual ontological and epistemological worldviews, encouraged conducting this qualitative, conceptual and philosophical research. The techniques chosen for this research are critical research techniques and methods. The Qur‘an, The Islamic Sunnah, The Bible, The Torah, and The Talmud, in addition to interviews with some professional accountants are the primary sources for this research. The major aim of this study is to play an effective role in the path of re-adopting of the Great Nest of Being, metaphysics and believing in the human being as a whole not just the human as a material. From the professional aspect, this study aims to propose an initial cure for the problem of separation between professional accountants' personal belief system (religion) and their professional conduct. This cure is to bring religious perspective in the professional codes of conduct through changing professional ethical normative theories from secular ethical theories to religion-based ethical theories. This cure has often been overlooked in the literature of international professional codes of conduct for professional accountants. These two goals are achieved through the following research objectives. First, contributing theoretically to the normative ethical theories by proposing a revised classification to these theories. Second, evaluating critically the international accounting codes of professional conduct based on the Divine command theory. Finally, proposing a new religion-based guide of ethics for accountants by refering to Abrahamic religions scriptures. This study concluded that IFAC code of ethics is a secular code and it is not based on a clear normative theory, thus it lacks supervision and accountability authorities. Moreover, it does not fulfil the theistic obligation of building ethical principles upon God's commands. This study suggested that the Divine command theory --as a consequentialist theory-- has the ability to influence the ethical behaviour of professionals, gives meaning to the ethical principles, and is not bound by the shortcomings of secular ethical theories. The results of the interviews validate the reclassification of the Divine command theory in normative theories and proved that there is consensus among interviewees, that believers have the obligation to follow God's commands. Nevertheless, there is shallowness in knowledge among interviewees in regard to normative ethical theories, descriptive ethics, and lack of awareness of fundamental axioms of their religion. Finally, proposing a religion-based guide of ethics for accountants help in making advantage of the characteristic of codes as ethical reminders. This guide is not a magic wand; nevertheless, it could be the bedrock for rebuilding an impartial profession.